Mass Media Target Audience and Mental Illness Stigmatization among Students of Kenya Medical Training College - Maina, Kamau; Riany, Kenneth Riany (Journal of Information Systems and Technology Research, 2023)
Mass media plays a fundamental role in influencing the society and their perceptions in daily life. The target audience by the media determines the how they frame their message and the subject matter that they focus on in their discussions. As mental illness is becoming one of the contemporary issues in the modern society, the role of mass media particularly how they define their target audience is not adequately explored. This is despite mental illness continuing to ravage the society, especially with the increased stigmatization. This study therefore sought to examine the how mass media target audience impact mental illness stigmatization in among students in Kenya Medical Training College. The study was anchored on the cognitive dissonance theory.  Using a descriptive research approach, the study through a questionnaire surveyed 384 students drawn from a population of 51045 students at the college. The data was analysed using descriptive and inferential statistics through SPSS. The findings revealed that mass media target audience through the reduced dissonance, acquisition of new information and cognitive actions significantly impacted the mental illness stigmatization. Through the beliefs towards the mentally ill persons as projected by the mass media to their target audience, the stigmatization of mentally ill persons either increased or decreased depending on the approach used by the mass media. The study concluded that mass media target audience was instrumental in determining the level of stigmatization of the mentally ill persons. It is therefore recommended that the mass media should define their target audience in a manner that positively changes their perceptions towards mental illness.